A review: antibacterial activities, antioxidant properties and toxicity profile of Centella asiatica - Ramli, Suzita; Wong, Jun Xian; Abdul Mutalib, Noor Azira (Universiti Pendidikan Sultan Idris, 2020)
Centella asiatica (C. asiatica) has been widely used as traditional or alternative medicine for thousand years due to its capabilities to cure various kinds of diseases. This plant has been used widely to prepare numerous kinds of food and beverages in many countries due to its beneficial functional properties. Active compounds that contribute to its antimicrobial properties are madecassic acid, asiatic acid, madecassoside, and asiaticoside. C. asiatica extract can inhibit majorities of foodborne pathogenic and spoilage microorganisms. It also contained antioxidant properties and has been proven to have an insignificant toxicity effect on human consumption. Currently, there is an increase of interest in research development for natural antioxidants and antimicrobial agents to replace the synthetic types in the food industry. This review presents information on the antioxidant capabilities of C. asiatica and its function to inhibit, reduce or minimize microbial growth. The toxicity and safety aspects of consuming C. asiatica extract has also been highlighted to provide essential data for the development of natural preservatives.